Enhancement of the advanced Fenton process by weak magnetic field for the degradation of 4-nitrophenol1. Issue 18 (5th March 2015) - Xiong, Xinmei; Sun, Yuankui; Sun, Bo; Song, Weihua; Sun, Jingyi; Gao, Naiyun; Qiao, Junlian; Guan, Xiaohong
<x xml:space="preserve">Abstract</x> A superimposed WMF could significantly improve the oxidative ability of Fe0/H2O2 and widen its applicable pH range.